THE EFFECT OF INFLATION, BI INTEREST RATES AND THE RUPIAH EXCHANGE RATE ON BANKING COMPANY SHARE PRICES ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2024 PERIOD - Ernawati Malik; Waode Nahra Nafiran (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to determine the effect of inflation, the BI interest rate (BI-Rate), and the rupiah exchange rate on the stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study uses a quantitative method with secondary data. The sample was determined using a purposive sampling technique based on certain criteria, resulting in 16 banking companies with a total of 64 observational data. The data analysis technique used was multiple linear regression with the help of SPSS 25. The results of the study partially indicate that inflation, interest rates, and the exchange rate, the three independent variables, have no significant effect on the stock prices of banking companies. Simultaneously, the three variables also have no effect. The Adjusted R Square value obtained was 0.042 or 4.2%, which means that only 4.2% of the stock price variation can be explained by the variables of inflation, the BI interest rate, and the exchange rate, while the remaining 95.8% is explained by other factors outside the research model.